Evaluation of Hospital Disaster Resilience - Amaliah, Rizqi Ulla; Sundaru, Agung; Jayati, Trisna (Newinera Publisher, 2024)
The purpose of this study is to develop fire management strategies at Hospital X in Batam City, Riau Islands. The research design to be used in this study is a qualitative method. Data indicates that Hospital X has an emergency response team; however, the number of certified employees is still below the standards set by the regulations. Although Hospital X conducts evacuation simulations and fire training annually, there are several shortcomings in the evacuation routes, including inappropriate handrail height and unpainted emergency exit doors. The evaluation also found that, despite the availability of fire-fighting facilities such as fire extinguishers and detectors, regular inspections are not conducted uniformly. The distance between fire extinguishers exceeds the stipulated 15 meters, which could increase the risk of fire. Based on these findings, it is recommended that the Occupational Health and Safety Team take corrective actions to ensure compliance with existing regulations, including enhancing employee certification and updating evacuation facilities. By implementing these recommendations, it is expected that Hospital X can improve disaster resilience, ensure the safety of patients and staff, and be prepared for future emergencies.